Effect of leaf characteristics of sweet gourd germplasms on the population abundance and infestation of epilachna beetle (Epilachna spp.) - Afroz, Mansura; Amin, Md Ruhul; Uddin Miah, Md Ramiz; Hossain, M Mofazzal (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
The phytophagous insect epilachna beetle (Epilachna spp.) is a threat to the cultivation of different cucurbit crops including sweet gourd (Cucurbita moschata). Host plant itself can influence the infestation of insect by different means. Therefore, investigations were done on the population abundance and infestation level of epilachna beetle on sweet gourd and to find out the relationship between the abundance of the beetle and the morphological as well as biochemical characteristics of the leaves. The study was conducted in the field and laboratory of the Department of Entomology, Bangabadhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh from July 2018 to June 2019 with 12 sweet gourd germplasms. Among the germplasms, BD 264 showed the lowest abundance of grub (3.1±0.3 grubs/ 3 leaves), and BD 264 and BD 266 revealed statistically similar and the lowest abundance of the adult beetles (1.7±0.1 adults/ 3 leaves in both the cases). The level of leaf infestation among the germplasms varied significantly and ranged from 6.2% to 16.4%. The abundance of adult beetles was positively correlated with the number of leaf plant-1, but leaf area and trichomes (r = -0.994 and -0.991 for BD 264 and BD 266, respectively) exerted negative relationship. Moisture (r = 0.998 for BD 269), total chlorophyll, reducing sugar and ash content (r = 0.997 for BD 269) in the leaves of the germplasms showed positive influence on the abundance of beetle, but protein content was negatively correlated. The leaf characteristics of sweet gourd which were found to be responsible to alter the infestation of Epilachna spp. can be incorporated in Integrated Pest Management (IPM) strategy.